Fast and quantitative manganese sorption by polyamidoamine resins. Issue 4 (27th November 2012) - Manfredi, Amedea; Ranucci, Elisabetta; Morandi, Sara; Mussini, Patrizia Romana; Ferruti, Paolo
Abstract : Two poly(amidoamine) crosslinked resins whose repeating units are mimics of L ‐lysine (LYMA) and of EDTA (LMT85) prove capable of quantitatively and reversibly sorbing manganese ions (Mn 2+ ). Halving times are on the order of 1 min or less, and Mn 2+ can be abated to the ppb level.